Profile Laboratory of Thalassemia in the General Hospital Dr. Zainoel Abidin Banda Aceh - Mutiawati, Vivi Keumala; Aman, Adi Koesoema (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2024)
Thalassemia refers to the globin gene abnormality that affects the a and b globin genes. A comprehensive peripheral blood laboratory examination, Mentzer index, blood morphology, and Hb analysis were all performed on every patient with thalassemia who attended treatment as part of this analytical observational study. This research aims to know the profile of laboratory examinations of thalassemia patients in the Dr. Zainoel Abidin General Hospital (RSUZA) Banda Aceh. The study's target population was 547 individuals, with 278 males and 269 females making up the male and female split, respectively (50.7% and 49.3%). With a total of 197 subjects (36.4%), this study revealed that the subjects were most frequently found in the age range of 0–5 years. Only 8 subjects, or 1.5%, of the population in the over-65 age group, were detected. The typical value of the erythrocyte index further fell and was discovered in 469 participants with a value of 85.3%. A total of 504 patients, or 91.6%, had more elevated RDW features. Results for the Mentzer index with 432 subjects were determined to be 13 were 78.5%. In the 450-subject hypochromic microcytic group, subjects were most frequently observed (81.8%). Blood morphology features from 505 participants, or 91.8% of the total, showed no additional blood morphology characteristics in normoblasts, and from 361 subjects, or 65.6% of the total, showed no target cells. When a person has anemia or a family history of thalassemia, it is strongly advised that they get a full blood count (CBC). The proper laboratory testing is still necessary for the health issue of thalassemia.